A Blueprint for Streamlining Patient Pathways Using a Hybrid Lean Management Approach. Issue 4 (October 2020) - Rizan, Chantelle; Low, Rob; Harden, Saskia; Groves, Nick; Flaherty, Breda; Welland, Trevor; Das, Prodip; Bhutta, Mahmood F.
Abstract : Background: Streamlining patient pathways within health care systems is a complex and challenging process. While frontline clinicians often have an abundance of ideas, these rarely translate into real-world change due to nonadoption or early abandonment. Objectives: The aim of this article is to provide frontline clinicians with a blueprint for developing a business case for a streamlined pathway while guiding the practical implementation of this blueprint. Methods: The key steps outlined in streamlining a patient pathway are as follows: step 1—identify problems with the patient pathway; step 2—identify the potential to streamline; step 3—forecast the benefits of the streamlined pathway; step 4—gain approvals; step 5—plan the practicalities; step 6—implement and monitor the streamlined pathway; and step 7—monitor the streamlined pathway. Within these steps, Lean management techniques are introduced (including value stream mapping, Pareto charts, Ishikawa diagrams, demand and capacity calculations, role lane mapping) and strengthened by other methods (retrospective audit, systematic review, patient questionnaires, and cost analysis). Results: This roadmap is contextualized using a case study, demonstrating how streamlining pathways can result in statistically significant reductions in referral to treatment time, the number of steps in the pathway, lead time (pathway duration), and handoff (transfer of patients between health care professionals). This can be achieved while increasing patient contact time, improving patient satisfaction, and reducing costs. Conclusion: This blueprint demonstrates a comprehensive method for streamlining patient pathways, using Lean management techniques complemented by additional methods. This approach was developed by frontline clinicians and can be replicated by others, translating quality improvement ideas into sustainable change in practice. It enables the design of streamlined pathways that confer significant benefits to patients, health care service providers, and the health economy. Abstract : Supplemental Digital Content is Available in the Text.